A new model to resolve technical problems. (September 2020) - Zhang, Shijun; Zhang, Teng; Wang, Haijie
Abstract: The Algorithm for Inventive Problem Solving (ARIZ) is a very good tool to solve complicated problems. However, it is fussy to get a specific solution under the guides of ARIZ in the Theory of Inventive Problem Solving (TRIZ). A novel approach to getting solutions for inventive problem solving in TRIZ is shown in this paper. A model named 5-R model of finding specific solutions was developed. 5-R model has four steps to obtain specific suggested solutions for technical problems. Reason-occurred-analysis is the first step in this new model. Then a clear statement of the Ideal Final Result is used to encourage breakthrough thinking and get solutions to the problem. After that, suggested resolutions can be obtained with the Contradiction Matrix, the Physical Contradiction, the Substance-Field, the Effects, Function Analysis, System Enhancement route, and Substance-Field Analysis. Finally, a reasonable specific solution for innovative problem solving can be gotten using resource analysis. 5-R model is not difficult to learn and remember. 5-R model improves the efficiency of getting solutions with TRIZ. Finally, a practical engineering problem was solved using this now model successfully.